Juridical Analysis of The Application of Emergency Constitutional Law During The Covid-19 Pandemic - Fitri Atur Arum (Ipso Jure, 2025)
The emergency situation raises concerns about potential abuses of power or human rights violations during the implementation of emergency measures. It is important to consider that emergency measures must be proportionate, non-discriminatory, and always take into account and protect the rights of citizens and the time frame for their resolution. This research is a normative legal research (normative juridical by examining literature materials with a secondary database to review the Covid-19 problem from the perspective of emergency constitutional law using a statutory approach (statue approach) by examining laws related to the issues being studied[1], conceptual approach, and comparative approach. This research produced findings, namely that there has been no regulation related to the term and supervision in Law 6/2018 and there have been no regulations related to the supervision of legislative institutions outside the trial forum and the period that regulates the enactment of the Perppu. Then., some emergency laws in Indonesia have not referred to Article 12 of the 1945 Constitution of the Republic of Indonesia, thus causing inconsistencies in the scope of the Emergency HTN in Indonesia.